2006
DOI: 10.1091/mbc.e05-07-0635
|View full text |Cite
|
Sign up to set email alerts
|

An Uncleavable uPAR Mutant Allows Dissection of Signaling Pathways in uPA-dependent Cell Migration

Abstract: Urokinase-type plasminogen activator (uPA) binding to uPAR induces migration, adhesion, and proliferation through multiple interactions with G proteins-coupled receptor FPRL1, integrins, or the epidermal growth factor (EGF) receptor (EGFR). At least two forms of uPAR are present on the cell surface: full-length and cleaved uPAR, each specifically interacting with one or more transmembrane proteins. The connection between these interactions and the effects on the signaling pathways activation is not clear. We h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
64
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 50 publications
6
64
2
Order By: Relevance
“…Resistance to uPAR cleavage in M6P/IGF2R knockdown cells might also have important implications for the nature of uPA signaling in these cells. Using a cleavageresistant mutant of uPAR Mazzieri et al (2006) showed that reduced cleavage of uPAR favored epidermal growth factor Figure 8. uPAR cleavage but not uPAR internalization and turnover is dependent on M6P/IGF2R expression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Resistance to uPAR cleavage in M6P/IGF2R knockdown cells might also have important implications for the nature of uPA signaling in these cells. Using a cleavageresistant mutant of uPAR Mazzieri et al (2006) showed that reduced cleavage of uPAR favored epidermal growth factor Figure 8. uPAR cleavage but not uPAR internalization and turnover is dependent on M6P/IGF2R expression.…”
Section: Discussionmentioning
confidence: 99%
“…The cleavage was almost completely blocked by the uPA inhibitor amiloride, a mixture of the serine protease inhibitors aprotinin and PMSF, and partially blocked by addition of PAI-1 (Supplemental Figure S4), indicating that the cleavage is mediated or initiated by active uPA. uPAR seems to be more cleaved when dimerized within lipid rafts (Cunningham et al, 2003) and complexed with integrins (Mazzieri et al, 2006). To what extend these observations explain the role of M6P/IGF2R in uPAR cleavage needs future investigations.…”
mentioning
confidence: 94%
“…Available data in cultured cancer cells, however, indicate that uPAR overexpression activates cell proliferation by interacting with integrins and with growth factor receptor tyrosine kinases like the EGF and the PDGF receptors (Liu et al, 2002;Kiyan et al, 2005). However, peptide a325 that dissociates uPAR-a3b1 and -a5b1 complexes (Wei et al, 2001;Mazzieri et al, 2006) had no effect on wt MEFs growth rate or ERK activation (data not shown). It is known that overexpression of uPAR in Hep3 cells, for example, modifies the response of the EGF-R to EGF, so that EGF-R was activated in the absence of EGF (Liu et al, 2002).…”
Section: )mentioning
confidence: 93%
“…On the other hand, direct experimental demonstration of uPAR/EGF-R functional interaction in vivo is still outstanding. In cell culture, on the other hand, different uPAR conformations are able to differentiate between different interacting proteins, that is, EGF-R or integrins (Mazzieri et al, 2006). A detailed mutation study of uPAR will uPAR regulates cell growth in primary embryo fibroblasts R Mazzieri et al probably allow to describe accurately the molecular mechanism (and interactors) involved in its role in growth control.…”
Section: )mentioning
confidence: 99%
“…A number of studies have demonstrated that suPAR binds directly to membrane proteins, such as FPRL1, and triggers cell signaling (6,(27)(28)(29). The nature of the signaling response may be determined by whether suPAR is cleaved between domain-1 and the domain-2-3 region, revealing the epitope, SRSRY, involved in FPRL1 binding (6,27,30). suPAR has been implicated in hematopoietic stem cell mobilization (31) and in the development of focal segmental glomerulosclerosis (32).…”
Section: Urokinase Receptor (Upar)mentioning
confidence: 99%